Exploring the Ligand Functionality, Electronic Band Gaps, and Switching Characteristics of Single Wells–Dawson‐Type Polyoxometalates on Gold (Adv. Mater. Interfaces 21/2022). Issue 21 (22nd July 2022) - Glöß, Maria; Pütt, Ricarda; Moors, Marco; Kentzinger, Emmanuel; Karthäuser, Silvia; Monakhov, Kirill Yu.
Abstract : Polyoxometalates Polyoxometalates (POMs) equipped with vanadium centers offer outstanding opportunities for the development of switchable molecularly functionalized surfaces for non‐binary, beyond‐CMOS memory chips. In article number 2200461, Maria Glöß, Silvia Karthäuser, Kirill Yu. Monakhov, and co‐workers report a room‐temperature, multistate resistive switch based on a V3 ‐substituted Wells‐Dawson‐type POM structure. The lilac spheres are unswitched POMs, the yellow sphere is switched POM.